2017
DOI: 10.1039/c7ra06442j
|View full text |Cite
|
Sign up to set email alerts
|

Membrane destruction-mediated antibacterial activity of tungsten disulfide (WS2)

Abstract: The antibacterial activities of tungsten disulfide (WS 2 ) nanosheets against two representative bacterial strains: Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus)were evaluated by colony-forming unit (CFU) studies. The WS 2 samples demonstrate a time and concentration dependent antibacterial activity (retardation of bacterial growth) for both bacterial strains.Morphology analyses reveal that WS 2 nanosheets adhere to the bacterial surfaces, resulting in robust inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 59 publications
(49 reference statements)
1
63
0
Order By: Relevance
“…Liu et al. reported that the antibacterial activity of WS 2 nanosheets mainly originates from induced structural damage rather than ROS generation . However, because the authors did not show the GSH oxidation data, it is difficult to judge whether the membrane disruption is caused by a physical interaction or ROS‐independent oxidative damage.…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…Liu et al. reported that the antibacterial activity of WS 2 nanosheets mainly originates from induced structural damage rather than ROS generation . However, because the authors did not show the GSH oxidation data, it is difficult to judge whether the membrane disruption is caused by a physical interaction or ROS‐independent oxidative damage.…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…While the direct use of sun light for photocatalytic bacterial disinfection might be attractive for low cost water treatment, the use of fluorescent light is more relevant for actual household applications to supply potable water. Antibacterial properties of WS 2 and rGO‐WS 2 nanosheet has also been investigated without using any light source . Luminescence activity has also been shown for WS 2 and MoS 2 with Ag nanoparticles based composite …”
Section: Introductionmentioning
confidence: 99%
“…The high antibacterial rates against S. aureus and E. coli indicated a quite high antibacterial efficiency of the WS 2 laminar membrane, even after short‐term contact (1 h). The proposed mechanism for this marked antibacterial property is that the WS 2 nanosheets retarded the bacterial growth by deformation of the bacterial cell and damage of the cell wall on the basis of the reported results …”
Section: Resultsmentioning
confidence: 78%